Energy Strategy for Rural India : Evidence from Six States - World Bank (Washington, DC, 2014)
The fieldwork for this report consisted of a household energy survey of households living in 180 villages in six states (Andhra Pradesh, Himachal Pradesh, Maharashtra, Punjab, Rajasthan and West Bengal). The report was initiated in response to concerns that energy strategies for rural India were not progressing toward modern energy use.It examines energy use, including renewable energy, to determine if households in rural areas have access to modern forms of energy use. In addition, analysis and recommendations are targeted toward poor households, who spend a significant proportion of their time and income on energy. Despite urbanization, 74 percent of India (some 120 million households) reside in rural areas, villagers still depend on traditional fuels to meet their energy needs. Fuelwood, crop residues, dung and other traditional fuels, as presently used, have inherent disadvantages: collection is arduous and time-consuming; combustion is difficult to control; and cooking captures a fraction of these fuels' available energy. Today, rural people who switch to kerosene and LPG for cooking spend about one hour per day collecting fuelwood and purchasing wood at local markets. The Government is committed to improving energy services in rural areas, however, the cross-sectoral nature of the problems complicates solutions.